Kepastian Hukum Larangan Notaris Merangkap Jabatan sebagai Pimpinan Badan Usaha (International Forum of Researchers and Lecturers, 2025)
The provision under Article 17 paragraph (1) letter f of the Notary Law (UUJN) stipulates that a Notary is prohibited from concurrently holding a position as a leader or manager in a state-owned or private business entity. However, the term